Muon-spin relaxation measurements on the dimerized spin-1/2 chains NaTiSi2O6 and TiOCl - Baker, P; Blundell, S; Pratt, F; Lancaster, T; Brooks, M; Hayes, W; Isobe, M; Ueda, Y; Hoinkis, M; Sing, M; Klemm, M; Horn, S; et al. (American Physical Society, 2007)
We report muon spin relaxation (μSR) and magnetic susceptibility investigations of two Ti3+ (S=1/2) chain compounds, NaTiSi2O6 and TiOCl, each of which exhibits a spin gap at low temperature. From these we conclude that the spin gap in NaTiSi2O6, which arises from orbital ordering at Too, with a value of 2Δ =700(100) K. In TiOCl, we find thermally activated spin fluctuations corresponding to a spin gap 2Δ=440(60) K below Tcl=67 K. We can describe both the μSR and susceptibility data in terms of a model based on the dimerization of the Ti3+ chains. We also compare the methods used to extract the spin gap and the concentration of free spins within the samples from μSR and magnetic susceptibility data.